Iyanu : child of wonder. Volume 3 - Okupe, Roye; Okupe, Roye (Dark Horse Books, 2023)
"Iyanu makes her way to the Source to save all of Yorubaland from an ancient curse. This time, however, she has help from her new friends: Biyi, a carefree adventurer; Toye, the bookworm; and Ekun, the magical and opinionated giant leopard! Together, all four--also known as Team Chosen--embark on an epic adventure full of twists, turns, and laughs that will change their lives forever!"--Publisher's website.